Digitalisasi Ekonomi UMKM sebagai Upaya Pemberdayaan Ekonomi Berkelanjutan di Masa Pandemi Covid-19 - Ristianti, Novia Sari; Bashit, Nurhadi; Martono, Kurniawan Teguh; Ulfiana, Destya (Jurnal Surya Masyarakat, 2023)
The Covid-19 pandemic has caused the Gubuk Tiwul MSME industry in Ngerangan Village, Bayat District, Klaten Regency, to experience a slump. The lack of knowledge of business actors about the development of digital technology has hampered the flow of buying and selling MSMEs in Gubuk Tiwul during the pandemic. Whereas the digitization of MSMEs is essential to create innovations in business that can make the economy survive and rise. Therefore, this community service activity aims to introduce a digital system to MSME business actors in managing and promoting Gubuk Tiwul MSME products. The activity method consists of 3 stages, namely the information stage, which aims to determine the current needs of the Gubuk Tiwul MSMEs; the guidance and practice stage, which seeks to implement the MSME digitization theory that has been given; and the habitual independence stage which aims to create the independence of business actors in sustainably running their business digitally. Business actors are provided with comprehensive materials starting from how to produce and distribute hygienic products, techniques for up-to-date packaging products, how to obtain product certification, product marketing techniques through social media or e-commerce, to how to manage finances effectively and efficiently through the system. Digital. The evaluation results show that the service activities have benefited MSME business actors in Gubuk Tiwul to manage and promote their products through a digital strategy.